2009
DOI: 10.1097/mnh.0b013e3283294b98
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria in children

Abstract: When considering the population as a whole, children make ideal subjects in which to study the natural history of albuminuria given their relative lack of multiple morbidities commonly seen in adults. The unfortunate rise in 'adult' diseases in the pediatric age group makes this especially relevant. There is a need for longitudinal studies examining predictors of elevated urinary albumin levels as well as potential treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 51 publications
2
58
1
3
Order By: Relevance
“…Mean values for eGFR and overall prevalence of microalbuminuria are in line with results of previous population-based studies in children of the same age range. 16,17 We used the urine albumin to creatinine ratio to evaluate albuminuria in a random urine sample. 18 Because the within-subject variation in urinary albumin excretion is large, the variability would probably be lower if we collected first morning void samples instead of random samples during the day.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Mean values for eGFR and overall prevalence of microalbuminuria are in line with results of previous population-based studies in children of the same age range. 16,17 We used the urine albumin to creatinine ratio to evaluate albuminuria in a random urine sample. 18 Because the within-subject variation in urinary albumin excretion is large, the variability would probably be lower if we collected first morning void samples instead of random samples during the day.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The study of albuminuria in adolescents before the onset of overt adult clinical disease, although currently limited to diabetic adolescents, (Rademacher et al, 2008;Rademacher and Sinaiko, 2009) is attractive allowing recognition of pro-atherosclerotic predictors in a free of disease-burden setting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to poor glycemic control, clinical markers of insulin resistance were associated with its development [44]. There might be also the influence of some genetic polymorphisms [39]. It has also been found out that children and adolescents with type 1 diabetes with borderline microalbuminuria are more than twice as likely to develop persistent microalbuminuria compared to normoalbuminuria [44].…”
Section: Microalbuminuria In Different Childhood Diseasesmentioning
confidence: 94%
“…Recently, normative data on albumin excretion in healthy adolescents have been published [38]. It has been found that in healthy children, albuminuria relates to fasting insulin, but not to blood pressure, body mass index, lipid levels, fasting glucose, or insulin resistance [38,39].…”
Section: Microalbuminuria In Healthy Childrenmentioning
confidence: 99%
See 1 more Smart Citation